Ameliorative Effect of Lycopene on Haematological Indices of Common Carp Cyprinus carpio, Linnaeus, 1758 Exposed to Cypermethrin - Yonar, M. Enis (My University, 2017)
The present study was conducted to investigate the effectiveness of lycopene inalleviating the toxicity of cypermethrin (CYP) on haematological parameters in carp,Cyprinus carpio. Fish (totally 140 fish) were exposed to sublethal concentrations (0.202and 0.404 ?g/L) of CYP, and lycopene (10 mg per kg of fish weight) was simultaneouslyadministered. At the end of 28 days administration, blood samples were collected andhaematological changes (red and white blood cell count, haemoglobin concentration,haematocrit level, and erythrocyte indices: mean corpuscular volume, mean corpuscularhaemoglobin, and mean corpuscular haemoglobin concentration) were determined.According to the data obtained, CYP was determined to lead to negative alterations in thehaematological parameters investigated. The administration of lycopene alleviated thiseffect.
Keywords: Biyoloji